COMPARATIVE INFLUENCE OF PEDAGOGICAL COMPETENCE AND WORK MOTIVATION ON TEACHER PROFESSIONALISM: EVIDENCE FROM EAST UNGARAN DISTRICT - Zulianti Lisa Kurniawati; AY Soegeng Ysh; ngurah ayu nyoman murniati (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study investigates the extent to which pedagogical competence and work motivation individually influence teacher professionalism in public elementary schools in East Ungaran District, Indonesia. Using a quantitative causal design, data were collected from 125 teachers selected through proportional random sampling and analyzed using correlation and linear regression techniques. The findings show that both pedagogical competence (β = 0.721, R² = 0.724) and work motivation (β = 0.785, R² = 0.743) have positive and significant partial effects on teacher professionalism. Notably, work motivation demonstrates a stronger influence, indicating that intrinsic and extrinsic motivational factors contribute more substantially to professional behavior than technical pedagogical skills alone. This study provides empirical evidence that strengthening internal drive and work climate may yield greater improvements in teacher professionalism than focusing solely on competency-based training. The results offer practical implications for policymakers and school leaders in designing targeted professional development strategies.